The Influence of Product Quality, Promotion and Brand Image on Brand Trust and Its Implication on Purchase Decision of Geprek Bensu Products - Yoesoep Edhie Rachmad; Dian Meliantari; Ilham Akbar; Syamsu Rijal; Muhammad Reza Aulia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The objective of this study is to examine how brand trust, product quality, brand image, and marketing strategies affect consumers' purchasing decisions. The sampling method utilized in this study was non-probability sampling, or purposive sampling. The distribution of questionnaires to 100 respondents who are residents of Jakarta, are older than 18, and have made at least three purchases of Geprek Bensu items served as the method for gathering data. Then, using SPSS Statistics version 29.0, path analysis was performed. The findings of this study show that brand trust affects buying decisions by having an impact on product quality. In contrast, brand trust has no bearing on the purchase decisions made by consumers.